A graphite electrode modified by diazotization grafting phenol layer on graphite surface and preparation method thereof
By diazogically grafting the phenol layer on the surface of graphite particles, the graphite/phenol layer composite is formed, which solves the problem of peeling off the graphite negative electrode under high magnification conditions, and improves the specific capacity, rate performance and cycle stability of the lithium battery.
Patent Information
- Application Number
- CN202210685782.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-16
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-06-16
AI Technical Summary
The existing graphite negative electrode is prone to peeling under high magnification conditions, resulting in rapid attenuation of lithium battery capacity, and the electrochemical performance is highly dependent on the electrolyte and insufficient stability.
The electrochemical performance of the graphite electrode is improved by grafting the phenol layer with a chemically covalent grafting of the phenol layer on the surface of the graphite particles.
It improves the specific capacity, rate performance and cycle stability of graphite negative electrode, extends the life of the lithium battery, and simplifies the preparation process.
Smart Images

Figure CN115172664B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage, relates to a modified graphite electrode and a preparation method thereof, and in particular to a graphite electrode material modified based on a diazotized grafted phenol layer on a graphite surface and a preparation method thereof. Background Art
[0002] Lithium batteries were first successfully developed by Sony Corporation of Japan in 1990. It embeds lithium ions into carbon (petroleum coke and graphite) to form a negative electrode (traditional lithium batteries use lithium or lithium alloy as the negative electrode). Graphite has always been the main negative electrode material for lithium batteries due to its high conductivity, high rate performance, small volume expansion rate after lithium insertion, and low cost. However, the electrochemical properties of graphite negative electrodes are highly dependent on the electrolyte of lithium batteries. For example, using ether, sulfone, and sulfoxide compounds as solvents can easily lead to graphite exfoliation, thereby causing lithium battery capacity decay and reduced life; even when running in the second-generation electrolyte with ethylene carbonate-ethyl methyl carbonate (EC-EMC) as a solvent, when the rate exceeds 1C, graphite is also prone to exfoliation, causing the lithium battery capacity to decay rapidly (Electrochemistry Communications, 97 (2018) 37-41). In order to improve the electrochemical stability of graphite negative electrodes, researchers have developed a variety of methods. For example, the use of new adhesives, reducing Li + The interaction strength with the solvent, the addition of additives and surface modification to the carbonate solvent using a high concentration electrolyte, etc. CN102903952A discloses a ternary composite negative electrode material lithium ion battery and a preparation method thereof, wherein the negative electrode material in the ternary composite negative electrode material lithium ion battery is: made of titanium oxide, titanium salt or titanium element as a titanium source, lithium salt as a lithium source, starch as a hard carbon precursor and expanded graphite, and includes the following components in parts by weight: 50 to 98 parts of hard carbon, 1.5 to 45 parts of lithium titanate, and 0.5 to 5.0 parts of expanded graphite.
[0003] CN201410340471.7 discloses a multi-component composite negative electrode material and a preparation method thereof, as well as a lithium-ion battery using the negative electrode material. The multi-component composite negative electrode material for lithium-ion batteries is a multi-shell core-shell structure, wherein the core is graphite and a nano-active substance coated on the graphite surface, the first shell is a conductive carbon material, the second shell is a nano-active substance, and the third shell is a conductive carbon material coating layer. The invention adopts a coating treatment technology to coat the graphite surface with a nano-active substance to obtain a first precursor; then the first precursor is subjected to surface composite modification using a conductive carbon material to obtain a second precursor; next, the nano-active substance is coated on the surface of the second precursor to obtain a third precursor; finally, the third precursor is coated and modified to obtain a multi-component composite electrode material. However, the preparation of the multi-component composite negative electrode material involves high-temperature heat treatment, crushing, screening, demagnetization and other processes, and the steps are cumbersome. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a modified graphite electrode and a preparation method thereof, and in particular relates to a modified graphite electrode material based on a diazotized grafted phenol layer on a graphite surface and a preparation method thereof. Based on the diazotized grafted phenol layer on a graphite surface, the specific capacity, rate performance and cycle stability of the graphite negative electrode can be improved simultaneously.
[0005] A method for preparing a modified graphite electrode, comprising the following steps:
[0006] 1) Preparation of Gr-Ph-x
[0007] a. Transfer appropriate amount of graphite and 4-aminophenol into anhydrous acetonitrile solution and stir for 0.5–1h under nitrogen protection to obtain mixed solution A;
[0008] b. Add an appropriate amount of tert-butyl nitrite to the mixed solution A, and stir at room temperature under nitrogen protection for 12-48 hours to obtain a mixed solution B;
[0009] c. The mixed solution B is subjected to solid-liquid separation, the liquid is recovered, and the solid is dried under vacuum conditions to obtain Gr-Ph-x.
[0010] 2) Preparation of Gr-Ph-x electrode sheets
[0011] S1. Take appropriate amount of Gr-Ph-x, acetylene black and polyvinylidene fluoride, transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;
[0012] S2. The slurry is evenly coated on the copper foil current collector, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours to obtain a Gr-Ph-x electrode sheet. The Gr-Ph-x electrode sheet is a modified graphite electrode.
[0013] The commercially available –1LiPF 6 A mixed solution of ethylene carbonate-dimethyl carbonate-diethyl carbonate was used as the electrolyte, a lithium sheet was used as the counter electrode, and a Gr-Ph-x electrode sheet was used as the working electrode. A R2032 button-type lithium battery was assembled, and a diaphragm was added between the lithium sheet and the working electrode to measure the electrochemical properties.
[0014] The present invention utilizes diazo chemistry to covalently graft a phenol layer on the surface of graphite particles to form a graphite / phenol layer composite, abbreviated as Gr-Ph-x, wherein Gr represents graphite, Ph represents the phenol layer, and x is the molar percentage of 4-aminophenol to graphite.
[0015] Preferably, in step a, the molar percentage of 4-aminophenol to graphite is 3 to 10. The 4-aminophenol refers to unoxidized 4-aminophenol colorless crystals.
[0016] The anhydrous acetonitrile described in step a is The analytically pure acetonitrile obtained after molecular sieve drying treatment includes: The mass / volume of molecular sieve and acetonitrile is 0.2 g mL –1 , the drying time is 5-7 days, and the drying temperature is room temperature.
[0017] The anhydrous acetonitrile solution in step a, wherein the mass / volume ratio of graphite to anhydrous acetonitrile is 0.006-0.012 g mL –1 .
[0018] The nitrogen protection in steps a and b, wherein the nitrogen flow rate is 5-20 mL min –1 .
[0019] The appropriate amount of tert-butyl nitrite in step b, wherein the molar ratio of tert-butyl nitrite to 4-aminophenol is (3-10):1.
[0020] The solid-liquid separation in step c is carried out by centrifugal separation or vacuum filtration separation.
[0021] As described in step c, drying is performed under vacuum conditions, wherein the vacuum degree is 0.09-0.1 MPa, the drying temperature is 60-80° C., and the drying time is 6-12 h.
[0022] Preferably, in step S1, the mass ratio of Gr—Ph-x, acetylene black and polyvinylidene fluoride is 8:1:1.
[0023] Gr-Ph-x powder in step S1, wherein x=3-10.
[0024] The working electrode in step S2, where the mass of Gr-Ph-x is 2–3 mg cm -2 .
[0025] In step S3, the separator is a Celgard 2400 microporous polypropylene membrane. The volume ratio of ethylene carbonate-dimethyl carbonate-diethyl carbonate is 1:1:1.
[0026] The present invention also provides a modified graphite electrode prepared by the above method,
[0027] From the Nyquist plots of different graphite anodes ( Fig. 20 ) can be seen, representing the charge transfer impedance (R ct ) decreases from 157.3Ω of the initial graphite to 105.9Ω of Gr-Ph-3, 63.7Ω of Gr-Ph-5, and 86.8Ω of Gr-Ph-10.
[0028] The Li∥Gr-Ph-x lithium battery using the modified graphite electrode was cycled 300 times at 1C ( Fig.23 ), the discharge capacity remains at 284–361 mA h g -1 , the capacity retention rate is 82.6–90.5%. Specifically, 300 cycles at 1C ( Fig.23 ), the discharge specific capacities of Gr-Ph-3, Gr-Ph-5 and Gr-Ph-10 were maintained at 284, 361 and 314 mA h g -1 , the capacity retention rates were 82.6%, 90.5% and 89.5% respectively.
[0029] Beneficial Effects
[0030] 1. The preparation method of the modified graphite electrode provided by the present invention has mild reaction conditions, simple process, and is easy for large-scale industrial production.
[0031] 2. The modified graphite electrode provided by the present invention has high electrochemical cycle stability and high capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 XRD pattern of Gr-Ph-x.
[0033] Figure 2 A partial magnified image of the XRD of Gr-Ph-x.
[0034] Figure 3 Mechanism of diazotization grafted phenol layer on graphite surface: (a) formation of 4-hydroxybenzene cation and 4-hydroxydiazonium benzene cation; (b) grafted phenol layer; (c) formation of Gr-Ph-x.
[0035] Figure 4 This is the SEM image of the initial graphite (low magnification).
[0036] Figure 5This is the SEM image of the initial graphite (high magnification).
[0037] Figure 6 This is the SEM image of Gr-Ph-3 (low magnification).
[0038] Figure 7 This is the SEM image of Gr-Ph-3 (high magnification).
[0039] Figure 8 This is the SEM image of Gr-Ph-5 (low magnification).
[0040] Fig. 9 This is the SEM image of Gr-Ph-5 (high magnification).
[0041] Fig.10 This is the SEM image of Gr-Ph-10 (low magnification).
[0042] Fig.11 This is the SEM image of Gr-Ph-10 (high magnification).
[0043] Fig.12 This is the TEM image of Gr-Ph-5.
[0044] Fig.13 For the corresponding Fig.12 High-resolution TEM image of the circled area.
[0045] Fig.14 The atomic percentage of C in Gr-Ph-5 changes with Ar + Variation curve of sputtering depth.
[0046] Fig.15 This is the FT-IR graph of the sample.
[0047] Fig.16 is the C1s spectrum of the sample.
[0048] Fig.17 N1s spectrum of the sample.
[0049] Fig.18 This is the O1s spectrum of the sample.
[0050] Fig.19 Cyclic voltammograms of different graphite anodes.
[0051] Fig. 20 Nyquist plots of different graphite anodes.
[0052] Fig.21 Charge and discharge curves of different graphite anodes at 0.1C.
[0053] Fig. 22 Rate performance diagram of different graphite anodes.
[0054] Fig.23 Cycling curves of different graphite anodes. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings. These embodiments are only for illustrating the technical solution of the present invention and cannot be regarded as limiting the content of the claims of the present invention.
[0056] 4-Aminophenol, acetonitrile, tert-butyl nitrite, and N-methylpyrrolidone in the examples were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., copper foil, acetylene black, polyvinylidene fluoride, and Celgard 2400 microporous polypropylene membrane were purchased from Taobao Jinghong New Energy, and graphite was purchased from Shenzhen Bettery New Energy Materials Co., Ltd.
[0057] The X-ray powder diffraction spectrum (XRD) was obtained by using a German Bruker D8 Advance powder diffractometer; the scanning electron microscope (SEM) was obtained by using a Japanese Hitachi Regulus8220 field emission scanning electron microscope; the transmission electron microscope (TEM) was obtained by using a Japanese JEOL JEM-2100 transmission electron microscope; the Auger electron spectrum (AES) was obtained by using a US ThermoFisher ESCALAB 250Xi-AER Auger electron spectrometer; the infrared spectrum (FT-IR) was obtained by using a US Nicolet10 infrared spectrometer; the X-ray photoelectron spectroscopy (XPS) was obtained by using a US Fisher Scientific ESCALAB Xi + The electrochemical properties of the sample electrodes were obtained by X-ray photoelectron spectrometer detection; the electrochemical properties of the sample electrodes were obtained by Shanghai Chenhua CHI760E electrochemical analyzer and Wuhan Landian LANHE CT2001A battery testing system.
[0058] Example 1
[0059] 1) Preparation of Gr-Ph-3, the steps are as follows:
[0060] a. Transfer 0.3 g (25 mmol) of graphite and 0.082 g (0.75 mmol) of 4-aminophenol to 25 mL of anhydrous acetonitrile solution and stir under nitrogen for 0.5 h to obtain a mixed solution A;
[0061] b. Add 0.9 mL (7.5 mmol) of tert-butyl nitrite to the mixed solution A and stir at room temperature under nitrogen for 12 h to obtain a mixed solution B;
[0062] c. The mixed solution B was centrifuged to recover the liquid and the solid was dried in a vacuum drying oven at 60°C (vacuum degree of 0.09-0.1MPa) for 12h to obtain Gr-Ph-3.
[0063] 2) Assembly of Li∥Gr-Ph-3 lithium battery:
[0064] S1. Take appropriate amount of Gr-Ph-3, acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;
[0065] S2. The slurry was evenly coated on the copper foil (current collector), and then placed in a vacuum drying oven and dried at 80°C for 12 hours to obtain a working electrode. The mass of Gr-Ph-3 is 2 mg cm -2 .
[0066] S3, commercially available 1 mol L –1 LiPF 6 A mixed solution of ethylene carbonate-dimethyl carbonate-diethyl carbonate (volume ratio of 1:1:1) was used as the electrolyte, a Celgard 2400 microporous polypropylene membrane was used as the separator, a lithium sheet was used as the counter electrode, and Gr-Ph-3 was used as the working electrode to assemble an R2032 button lithium battery.
[0067] Example 2
[0068] 1) Preparation of Gr-Ph-5, the steps are as follows:
[0069] a. Transfer 0.3 g (25 mmol) of graphite and 0.136 g (1.25 mmol) of 4-aminophenol to 50 mL of anhydrous acetonitrile solution and stir under nitrogen for 1 h to obtain a mixed solution A;
[0070] b. Add 0.9 mL (7.5 mmol) of tert-butyl nitrite to the mixed solution A and stir at room temperature under nitrogen for 24 h to obtain a mixed solution B;
[0071] c. The mixed solution B was separated by filtration, the liquid was recovered, and the solid was dried in a vacuum drying oven at 70°C (vacuum degree of 0.09-0.1MPa) for 10 hours to obtain Gr-Ph-5.
[0072] 2) Assembly of Li∥Gr-Ph-5 lithium battery:
[0073] S1. Take appropriate amount of Gr-Ph-5, acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;
[0074] S2. The slurry was evenly coated on the copper foil (current collector), and then placed in a vacuum drying oven and dried at 80°C for 12 hours to obtain a working electrode. The mass of Gr-Ph-5 is 2.5 mg cm -2 .
[0075] S3, commercially available 1 mol L –1 LiPF 6 A mixed solution of ethylene carbonate-dimethyl carbonate-diethyl carbonate (volume ratio of 1:1:1) was used as the electrolyte, a Celgard 2400 microporous polypropylene membrane was used as the separator, a lithium sheet was used as the counter electrode, and Gr-Ph-5 was used as the working electrode to assemble an R2032 button lithium battery.
[0076] Example 3
[0077] 1) Preparation of Gr-Ph-10, the steps are as follows:
[0078] a. Transfer 0.3 g (25 mmol) of graphite and 0.272 g (2.5 mmol) of 4-aminophenol to 50 mL of anhydrous acetonitrile solution and stir under nitrogen for 1 h to obtain a mixed solution A;
[0079] b. Add 0.9 mL (7.5 mmol) of tert-butyl nitrite to the mixed solution A and stir at room temperature under nitrogen for 48 h to obtain a mixed solution B;
[0080] c. The mixed solution B was separated by filtration, the liquid was recovered, and the solid was dried in a vacuum drying oven at 80°C (vacuum degree of 0.09-0.1MPa) for 6 hours to obtain Gr-Ph-10.
[0081] 2) Assembly of Li∥Gr-Ph-10 lithium battery:
[0082] S1. Take appropriate amounts of Gr-Ph-10, acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, drop appropriate amounts of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;
[0083] S2. The slurry was evenly coated on the copper foil (current collector), and then placed in a vacuum drying oven and dried at 80°C for 12 hours to obtain a working electrode. The mass of Gr-Ph-10 is 3 mg cm -2 .
[0084] S3, commercially available 1 mol L –1 LiPF 6 A mixed solution of ethylene carbonate-dimethyl carbonate-diethyl carbonate (volume ratio of 1:1:1) was used as the electrolyte, a Celgard 2400 microporous polypropylene membrane was used as the separator, a lithium sheet was used as the counter electrode, and Gr-Ph-10 was used as the working electrode to assemble an R2032 button lithium battery.
[0085] Results Analysis
[0086] Figure 1 is the XRD pattern of graphite sample. Figure 1It can be seen that there are 7 diffraction peaks in the initial graphite, corresponding to the space groups P6 and 3 / mmc(194) hexagonal graphite (PDF#41-1487) (002), (100), (101), (004), (103), (110) and (112) planes. The XRD spectrum of the surface diazotized graphite sample is different from that of the initial graphite in that: (1) a new diffraction peak appears at 17.9°; (2) the intensity of each diffraction peak decreases; (3) the (00l) crystal plane shifts to the low angle region ( Figure 2 ). The new peak at 17.9° is attributed to the phenol layer after diazotization. The decrease in the intensity of each diffraction peak after diazotization is attributed to the coating of graphite by the phenol layer. The movement of the (00l) crystal plane in the low-angle region is attributed to the expansion of the interlayer spacing of the graphite (00l) crystal plane. This shows that the covalent grafting effect of phenol on the graphite surface defect site ( Figure 3 ) can expand the distance between graphite layers, which is beneficial to improving the rate performance of Gr-Ph-x because the lithium ions tend to be inserted and removed from the graphite layers in a direction parallel to the (00l) crystal plane (ASC Nano, 7 (2013) 2773–2780).
[0087] Before the diazotization reaction, the surface of graphite particles is relatively smooth ( Figure 4 ), but there are slight cracks ( Figure 5 After diazotization, as x increases to 3, the surface roughness of graphite particles decreases significantly ( Figure 6 ), no cracks were observed Figure 7 As x increases to 5, the surface of graphite particles becomes smooth and dense ( Figure 8 and Fig. 9 ). As x continues to increase to 10, the surface of the graphite particles becomes rough and porous ( Fig.10 and Fig.11 )). SEM results show that the surface structure of graphite can be regulated by changing the molar percentage of 4-aminophenol to graphite. A smooth and dense surface is conducive to the subsequent formation of a stable SEI (solid electrolyte interface).
[0088] Using TEM technology ( Fig.12 ), the modified layer on the surface of graphite particles can be observed, and the interplanar spacing of graphite can be measured. Taking Gr-Ph-5 as an example, the interplanar spacing of its (002) crystal plane is measured to be 0.347nm, which is larger than the 0.335nm of the initial graphite ( Fig.13 ), which shows that after diazotization, the spacing between graphite (00l) planes is indeed enlarged, which is consistent with the XRD results. Fig.13 It can be judged that the thickness of the phenol layer is 2–6 nm.
[0089] The thickness of the phenol layer can be further estimated using AES depth analysis. Fig.14 The effects of the atomic percentage of carbon in Gr-Ph-5 on Ar + The variation curve of sputtering depth. Fig.14 It can be seen that with the increase of sputtering depth, the content of carbon element gradually increases and stabilizes at a sputtering depth of about 6nm. This shows that the thickness of the phenol layer is about 6nm, which is consistent with Fig.13 The results are consistent.
[0090] The phenol layer on the graphite surface can be analyzed using FT-IR technology. Fig.15 This is the FT-IR image of the sample. Located at 3300, 1381, 1116–1004 cm –1 The peaks at 3430cm and 3470cm are respectively attributed to O–H stretching vibration, O–H in-plane bending vibration and C–O / C–OH stretching vibration (Acta Chimica Slovenica, 52 (2005) 238–244; Journal of Heterocyclic Chemistry, 54 (2017) 758-763); this indicates that the initial graphite surface contains hydroxyl functional groups. After surface diazotization, the intensity of the characteristic peaks related to phenol is significantly enhanced, such as OH stretching vibration (3430cm -1 ), CO stretching vibration (1116cm -1 ) and benzene ring breathing vibration peak (1506-1634cm -1 )(Journal of Heterocyclic Chemistry, 54(2017)758-763).
[0091] Table 1 Peak positions and contents of each component in C 1s, N 1s, and O 1s
[0092]
[0093] Furthermore, the formation of the phenol layer on the graphite surface was supported by the results of high-resolution XPS spectra of C1s, N 1s and O1s. Fig.16 ), the fitting peaks at 284.8, 285.1 and 286.2 eV correspond to C=C, CC(N,O) and C=O components respectively (Environmental Science&Technology, 50(2016)10978-10987). Fig.17 ), the fitting peaks at 399.6 and 400.2 eV correspond to NC and N=N components respectively (Langmuir, 23 (2007) 11074-11082). Fig.18), the fitting peaks at 530.5, 532.0 and 533.4 eV correspond to C=O, C-OH (C) and surface adsorbed oxygen (O a )(Journal of Materials Chemistry A, 3(2015) 21257-21268). It should be noted that with the increase of x value in Gr-Ph-x, the N 1s and O1s peak intensities gradually increase, which is attributed to the increase in the thickness of the phenol layer containing azo bonds and phenolic hydroxyl groups ( Figure 3 ). In addition, as the x value increases, the content of C=C component in C 1s decreases, while the content of CN component and CO component in O1s increases (Table 1); these results all indicate that the thickness of the phenol layer increases with the increase of x value.
[0094] Based on the above analysis of the results, the present invention uses diazo chemistry to grow a phenol layer on the surface of graphite particles, and controls the molar percentage of 4-aminophenol / graphite, so as to achieve the regulation of the thickness of the phenol layer and the surface roughness of the graphite particles; this lays a foundation for studying the influence of diazo grafted phenol on the graphite surface on its electrochemical properties.
[0095] Fig.19 The cyclic voltammetry (CV) diagrams of different graphite anodes are given. The reduction peak starting at 1.1V and centered at about 0.71V in the first cycle of the CV curve is attributed to the decomposition of the electrolyte and the formation of SEI (Journal of The Electrochemical Society, 151 (2004) A1659; The Journal of Physical Chemistry C, 118 (2014) 6586-6593); the reduction peak at 0.15V and below is attributed to Li + embedded in the graphite interlayer; the oxidation peak at 0.26V is attributed to the delithiation of graphite (The Journal of Physical Chemistry C, 118 (2014) 6586-6593). The main difference between Li∥Gr-Ph-x and the initial graphite negative electrode is that Li + The distance between the insertion and extraction peaks is shortened, and the intensity of the solvent irreversible reduction peak at 0.71 V is weakened. This shows that the surface diazo grafted phenol layer improves the Li + The reversibility of the deintercalation reaction and the stability of the electrochemical reaction in the electrolyte (Electrochimica Acta, 47 (2002) 1423-1439).
[0096] The surface diazo grafted phenol layer also improves the kinetics of the graphite electrode reaction. From the Nyquist plots of different graphite anodes ( Fig. 20) can be seen, representing the charge transfer impedance (R ct ) decreased from 157.3Ω of the initial graphite to 105.9Ω of Gr-Ph-3, 63.7Ω of Gr-Ph-5, and 86.8Ω of Gr-Ph-10. ct The decrease of means the improvement of electrode reaction kinetics, that is, the improvement of electrode rate performance. This shows that the diazotized grafted phenol layer can improve the rate performance of graphite. In addition, with the increase of x value, R ct There is a phenomenon of first decreasing and then increasing, which is attributed to Li + The deintercalation rate is not linearly related to the increase of phenol layer thickness; it also shows that the appropriate phenol layer structure (roughness) and thickness are more conducive to Li + of disembedding.
[0097] It is worth mentioning that the diazotized grafted phenol layer can not only improve the rate performance of the graphite anode, but also improve its specific capacity and cycle stability. For example, at 0.1C (1C = 372 mA g -1 ), the discharge specific capacity and coulombic efficiency (CE) of Gr-Ph-x are improved ( Fig.21 ). At different current densities, Gr-Ph-x exhibits a higher specific capacity than the initial graphite ( Fig. 22 ); and after the current density gradually increased from 0.1C to 5C and then back to 0.1C, Gr-Ph-x showed higher specific capacity and capacity retention rate than the initial graphite.
[0098] Cycle 300 times at 1C ( Fig.23 ), the discharge specific capacities of Gr-Ph-3, Gr-Ph-5 and Gr-Ph-10 were maintained at 284, 361 and 314 mA h g -1 The capacity retention rates were 82.6%, 90.5% and 89.5%, respectively, which were much higher than the initial graphite retention capacity (156 mA h g -1 ) and capacity retention rate (54.2%).
[0099] In summary, the present invention uses diazo chemistry to covalently graft a phenol layer on the surface of graphite particles, providing a method with mild reaction conditions, controllable process, and easy scale-up to improve the electrochemical performance of graphite negative electrodes. The present invention provides a modified graphite electrode based on diazo grafting of a phenol layer on the graphite surface and a preparation method thereof, which not only prevents direct contact between graphite and electrolyte, inhibits excessive decomposition of electrolyte and graphite stripping, and improves the electrochemical cycle stability of graphite by forming a phenol protective layer, but also the grafted phenol layer can improve electrode kinetics, realize electrochemical energy storage by utilizing the tautomerism of the quinone / phenol structure during the charge / discharge process, and improve the rate performance and charge / discharge specific capacity of graphite.
Claims
1. A method for preparing a modified graphite electrode, comprising the following steps: 1) Preparation of Gr-Ph-x a. Transfer graphite and 4-aminophenol to anhydrous acetonitrile solution and stir for 0.5-1h under nitrogen protection to obtain a mixed solution A; b. Add tert-butyl nitrite to the mixture A and stir at room temperature under nitrogen for 12-48h to obtain a mixture B; c. subjecting the mixed solution B to solid-liquid separation, recovering the liquid, and drying the solid under vacuum conditions to obtain Gr-Ph-x; Gr-Ph-x is an abbreviation for a graphite / phenol layer composite, wherein Gr represents graphite, Ph represents a phenol layer, and x is the molar percentage of 4-aminophenol to graphite, and x=3-10; 2) Preparation of modified graphite electrode S1: Take Gr-Ph-x, acetylene black and polyvinylidene fluoride, transfer them to an agate mortar, add N-methylpyrrolidone dropwise, grind them thoroughly, and prepare a slurry; S2: The slurry is evenly coated on the copper foil current collector, and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a Gr-Ph-x electrode sheet.
2. The preparation method according to claim 1, characterized in that The anhydrous acetonitrile described in step a is The analytically pure acetonitrile obtained after molecular sieve drying treatment includes: The mass / volume of molecular sieve and acetonitrile is 0.2 g mL -1 , the drying time is 5-7 days, and the drying temperature is room temperature; In step a, the mass / volume ratio of graphite to anhydrous acetonitrile is 0.006-0.012 g mL -1 .
3. The preparation method according to claim 1, characterized in that: The nitrogen protection in steps a and b, the nitrogen flow rate is 5-20mL min -1 ; In step b, the molar ratio of tert-butyl nitrite to 4-aminophenol is (3-10):
1.
4. The preparation method according to claim 1, characterized in that: The solid-liquid separation in step c, wherein the separation method is centrifugal separation or vacuum filtration separation; The vacuum conditions in step c are as follows: vacuum degree is 0.09-0.1 MPa, drying temperature is 60-80° C., and drying time is 6-12 h.
5. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of Gr-Ph-x, acetylene black and polyvinylidene fluoride is 8:1:
1.
6. The preparation method according to claim 1, characterized in that: The working electrode in step S2 has a mass of 2-3 mg cm -2 .
7. The preparation method according to claim 1, characterized in that: In step S3, the separator is a Celgard 2400 microporous polypropylene membrane, and the volume ratio of ethylene carbonate-dimethyl carbonate-diethyl carbonate is 1:1:
1.
8. A modified graphite electrode prepared by the method according to any one of claims 1 to 7.
9. The modified graphite electrode according to claim 8, characterized in that The Nyquist plot of the graphite negative electrode represents the charge transfer impedance (R ct ) decreases from 157.3Ω of the initial graphite to 105.9Ω of Gr-Ph-3, 63.7Ω of Gr-Ph-5, and 86.8Ω of Gr-Ph-10.
10. The modified graphite electrode according to claim 8 or 9, characterized in that: The Li∥Gr-Ph-x lithium battery assembled with the modified graphite electrode was cycled 300 times at 1C, and the discharge specific capacity was maintained at 284-361 mA h g -1 , the capacity retention rate is 82.6-90.5%.
11. The modified graphite electrode according to claim 10, characterized in that After 300 cycles at 1C, the discharge specific capacities of Gr-Ph-3, Gr-Ph-5, and Gr-Ph-10 remain at 284, 361, and 314 mA h g, respectively. -1 , the capacity retention rates were 82.6%, 90.5% and 89.5% respectively.
Citation Information
Patent Citations
Lithium ion battery adopting ternary composite cathode material and preparation method thereof
CN102903952A
Multi-component composite negative electrode material, preparation method of multi-component composite negative electrode material and lithium ion battery comprising multi-component composite negative electrode material
CN104091934A